Drug delivery and controlled release from biocompatible metal–organic frameworks using mechanical amorphization. Issue 47 (18th November 2016) - Orellana-Tavra, Claudia; Marshall, Ross J.; Baxter, Emma F.; Lázaro, Isabel Abánades; Tao, Andi; Cheetham, Anthony K.; Forgan, Ross S.; Fairen-Jimenez, David
Abstract : We have used a family of Zr-based metal–organic frameworks (MOFs) with different functionalized (bromo, nitro and amino) and extended linkers for drug delivery. Abstract : We have used a family of Zr-based metal–organic frameworks (MOFs) with different functionalized (bromo, nitro and amino) and extended linkers for drug delivery. We loaded the materials with the fluorescent model molecule calcein and the anticancer drug α-cyano-4-hydroxycinnamic acid (α-CHC), and consequently performed a mechanical amorphization process to attempt to control the delivery of guest molecules. Our analysis revealed that the loading values of both molecules were higher for the MOFs containing unfunctionalized linkers. Confocal microscopy showed that all the materials were able to penetrate into cells, and the therapeutic effect of α-CHC on HeLa cells was enhanced when loaded (20 wt%) into the MOF with the longest linker. On one hand, calcein release required up to 3 days from the crystalline form for all the materials. On the other hand, the amorphous counterparts containing the bromo and nitro functional groups released only a fraction of the total loaded amount, and in the case of the amino-MOF a slow and progressive release was successfully achieved for 15 days. In the case of the materials loaded with α-CHC, no difference was observed between the crystalline and amorphous form of the materials. These results highlight the necessity of a balance between the pore size of the materials and the size of the guest molecules to accomplish a successful and efficient sustained release using this mechanical ball-milling process. Additionally, the endocytic pathway used by cells to internalize these MOFs may lead to diverse final cellular locations and consequently, different therapeutic effects. Understanding these cellular mechanisms will drive the design of more effective MOFs for drug delivery applications.